Analysis of the Mathematical Concept Understanding Ability of VII Grade Junior High School Students - Tuti Alawiyah Prastiwi Damanik; Eva Julyanti; Laili Habibah Pasaribu (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kristen Indonesia, 2025)
This study aims to analyze the mathematical concept understanding ability of seventh grade students at SMP Swasta Bhayangkari 3 Rantauprapat regarding the topic of two-dimensional quadrilaterals. The assessment of concept understanding focuses on determining the extent of students' abilities in solving problems related to mathematical concepts, using the following indicators: Understanding mathematical concepts includes the ability to define a concept both verbally and in writing, group objects based on certain properties, provide examples and counter-examples of a concept, present the concept in various forms of representation, and apply concepts or algorithms to solve problems. The research method used is descriptive qualitative, involving 24 students as research subjects. Data were collected through a concept understanding test consisting of 5 questions related to two-dimensional quadrilaterals. The results indicate that 8 students, or 33.3%, are categorized as having high understanding, 12 students, or 50%, are in the moderate category, and 4 students, or 16.6%, fall into the low category. Thus, the mathematical concept understanding ability of the students is considered to be quite good. The research results show that students' understanding of mathematical concepts still needs to be improved, especially in the ability to explain concepts, clarify the nature of objects, and present concepts in various representations.